Pengadaan Tanah dalam Pembangunan Hunian Tetap Pascabencana di Kelurahan Talise, Kota Palu - Meraldha, Arsha Riyantikha; Virant Pangkerego, Gabriel Efod (Publikasi Indonesia, 2025)
The research provides significant insights for post-disaster regional planning, land conflict management, and agrarian policy implementation in Indonesia. Permanent housing development is a crucial element in post-disaster rehabilitation and reconstruction. This study examines land acquisition in Talise Village, Palu City, addressing disputes involving the government, a company holding Building Use Rights (HGB), and local communities. The disputes stem from land claims by residents who have cultivated the land for decades without formal ownership documents. Employing a descriptive qualitative approach, this research explores issues of legal certainty, land acquisition policies, and conflict resolution strategies. Findings emphasize the necessity of inclusive agrarian reform, participatory policies, and enhanced transparency in the land acquisition process. This study also highlights the potential of land-sharing concepts to effectively address the interests of stakeholders, including the government and affected communities. Key recommendations of this study are to accelerate land registration, strengthen the management of customary land, and develop adaptive policies for post-disaster needs. These findings aim to support better decision-making in land management in disaster-affected areas.